Internalisasi Moderasi Beragama di Lembaga Pendidikan Menengah Atas di Kalimantan Timur - Duraesa, M. Abzar; Idris, Muhammad (FENOMENA, 2021)
In Indonesia, religious moderation is now a topic of serious discussion. The religion most commonly associated with religious moderation in this country is Islam, which is a major religion. Long before the Ministry of Religion formalized the idea of religious moderation, moderate Islam and religious moderation as a topic for scientific inquiry were actually studied. In the context of schools, the way that religious moderation is implemented in schools varies depending on the organizational structure and management style of the educational institution. Senior high schools under the jurisdiction of the Ministry of Religion typically have a more visible implementation of their policies in all areas, including extracurricular activities, various subjects, the religious curriculum, and various narratives expressed by institutional leaders. This article addresses how much Islamic moderation discourse has permeated Indonesian Islamic education, particularly in senior high schools.